Pion to upsilon from kappa-deformed Poincare phenomenology - Dey, J.; Dey, M.; Ferreira, P. L.; Tomio, L. (Elsevier B.V., 1996)
In the extreme rarity of meaningful results for four dimensional physics produced from the mathematically very well developed theory of quantum groups, we present a phenomenological fit to the rotational and radial excitations of mesons with very few parameters, From pion to upsilon, the heavy and light mesons are fitted with the same degree of precision.